Three-dimensional optical transfer functions in the aberration-corrected scanning transmission electron microscope. - Jones, L; Nellist, P (2014)
In the scanning transmission electron microscope, hardware aberration correctors can now correct for the positive spherical aberration of round electron lenses. These correctors make use of nonround optics such as hexapoles or octupoles, leading to the limiting aberrations often being of a nonround type. Here we explore the effect of a number of potential limiting aberrations on the imaging performance of the scanning transmission electron microscope through their resulting optical transfer functions. In particular, the response of the optical transfer function to changes in defocus are examined, given that this is the final aberration to be tuned just before image acquisition. The resulting three-dimensional optical transfer functions also allow an assessment of the performance of a system for focal-series experiments or optical sectioning applications.